EKSPLORASI ETNOMATEMATIKA PADA STRUKTUR DAN MEKANISME ALAT TENUN TRADISIONAL GEDOGAN KARO - Lubis, Ulfa Annisa; Maharani, Israq; Rizqi, Nur Rahmi; Putri, Jihan Hidayah (FKIP Universitas Al Washliyah Medan, 2026)
This study aims to explore and describe the mathematical concepts embedded within the Gedogan Karo weaving loom at the Jamin Gintings National Hero Museum. The primary focus is to identify the application of ethnomathematics in the tool's structure and the process of weaving traditional Karo cloth (Uis Karo). The methodology employed in this research is qualitative with an ethnographic approach. Data were collected through direct observation of artifacts in the museum, technical documentation, and a literature study regarding the weaving techniques of the Karo people to dissect the underlying mathematical elements. The results and discussion indicate an integration of formal mathematical concepts across four main aspects: (1) Geometry, through the formation of parallel lines in the warp threads and perpendicular relationships in the weft threads; (2) Geometric Transformation, evident in the symmetry, reflection, and translation patterns of the Uis Karo motifs; (3) Binary Logic, in the thread-lifting technique that resembles computer algorithm systems; and (4) Trigonometry, in the thread tension mechanism which depends on the leaning angle of the weaver's body. The conclusion of this study is that the Gedogan Karo loom is a manifestation of local wisdom that intuitively applies complex mathematical principles. The author suggests that these ethnomathematical exploration results be integrated into the formal mathematics education curriculum as contextual learning material. This is crucial for increasing students' interest in mathematics while simultaneously strengthening efforts to preserve Karo cultural heritage in the modern era.